1999
DOI: 10.1111/j.1572-0241.1999.01529.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Trimethoprim-Sulfamethaxazole in Blastocystis Hominis Infection

Abstract: These results suggested that B. hominis may be pathogenic, especially when it is present in large numbers, and TMP-SMX is highly effective against this organism. Although there are some anecdotal reports, to our knowledge this is the first study examining the effect of TMP-SMX on B. hominis in humans.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
29
0
2

Year Published

2006
2006
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(35 citation statements)
references
References 20 publications
4
29
0
2
Order By: Relevance
“…Clinical features related to B. hominis include nausea, anorexia, abdominal pain, flatulence, and acute or chronic diarrhea (8). However other studies state an opponent view point and it is believed that other factors probably are the causing agents of these symptoms (7,(9)(10)(11).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Clinical features related to B. hominis include nausea, anorexia, abdominal pain, flatulence, and acute or chronic diarrhea (8). However other studies state an opponent view point and it is believed that other factors probably are the causing agents of these symptoms (7,(9)(10)(11).…”
Section: Introductionmentioning
confidence: 99%
“…The pathogenicity of B. hominis still has been debated. There are some reports supporting the pathogenic potential of this parasite (7). Clinical features related to B. hominis include nausea, anorexia, abdominal pain, flatulence, and acute or chronic diarrhea (8).…”
Section: Introductionmentioning
confidence: 99%
“…The pathogenicity of B. hominis still has been debated. A report supporting the pathogenic potential of this parasite (Ok et al, 1999); that can be found in patients with or without gastrointestinal symptoms. Some of the symptoms associated with Blastocystis infection include abdominal pain, constipation, and diarrhea, alternating diarrhea and constipation and others (Qadri et al, 1989).…”
mentioning
confidence: 99%
“…Eradikasyonun sağlanmaması durumunda D. fragilis için hastaya aynı dozda ikinci bir seknidazol kürü verilmesi, Blastocystis spp. için ise trimetoprim-sulfametaksazol (320 mg TMP, 1600 mg SMX) 7 gün verilmesi planlanmıştır (22). Sağaltım tamamlandık-tan bir hafta sonra kontroller tekrarlanmıştır.…”
Section: Introductionunclassified